High Level of the Fibrin Degradation Products at Admission Predicts Parenchymal Hematoma and Unfavorable Outcome of Ischemic Stroke After Intravenous Thrombolysis - Liu, Chang; Zhang, Yun; Niu, Lingchuan; Li, Jiani (Frontiers in Neurology, 2022)
Background and Purpose We aim to investigate whether the higher admission fibrin degradation products (FDPs) levels are associated with parenchymal hematomas (PHs) and unfavorable outcome after intravenous thrombolysis (IVT). Methods Consecutive patients with acute ischemic stroke treated with IVT were studied. The FDP level was obtained on admission. PH was evaluated 24 h after treatment. The unfavorable outcome was defined as a 90-day modified Rankin Scale >2. The multivariable linear stepwise regression was used to assess independent factors associated with the log-transformed FDP (lgFDP). The receiver operating characteristics (ROCs) curve analysis was used to determine the predictive value of the FDP level for PH and unfavorable outcome. The logistic regression was used to identify independent predictors for PH and unfavorable outcome. The mediation analyses were performed to investigate associations among the FDP level, PH, and outcome. Results A total of 181 patients were included in the final analyses [median age, 73 (63–79) years; 102 (56.4%) males; and the median baseline National Institutes of Health Stroke Scale (NIHSS) score, 8 (5–15)]. The lgFDP was independently associated with age (B = 0.011, 95% CI 0.006–0.015, p < 0.001) and the baseline NIHSS score (B = 0.016, 95% CI 0.008–0.025, p < 0.001). The FDP was positively associated with PH [odds ratio (OR) 1.034, 95% CI 1.000–1.069; p = 0.047]. According to the ROC analysis, the best discriminating factor for unfavorable outcome was the FDP ≥3.085 μg/ml. The FDP ≥3.085 μg/ml was an independent predictor of unfavorable outcome (OR 7.086, 95% CI 2.818–17.822; p < 0.001). Mediation analysis revealed that the association of the FDP ≥3.085 μg/ml with unfavorable outcome was not mediated by PH (p = 0.161). Conclusion The admission FDP levels can predict PH and unfavorable outcome in patients with acute ischemic stroke after IVT. PH does not mediate the effect of the FDP level on the outcome.